PEGylated exenatide injection (PB-119) improves beta-cell function and insulin resistance in treatment-naïve type 2 diabetes mellitus patients - Liu, Xu; Song, Ling; Zhang, Yuanhui; Li, Haiyan; Cui, Cheng; Liu, Dongyang (Frontiers in Pharmacology, 2023)
Objective: PB-119, a PEGylated exenatide injection, is a once-weekly glucagon-like peptide-1 receptor agonist. In the present study, we aimed to evaluate the effects of PB-119 on insulin resistance and beta-cell function in Chinese patients with type 2 diabetes mellitus (T2DM) to uncover its antidiabetic characteristics.Methods: A total of 36 Chinese T2DM patients were randomized to receive 25 μg and 50 μg PB-119 once weekly and exenatide (5-10 μg injected under the skin 2 times a day adjusted by the doctor) for 12 weeks. Oral mixed meal tolerance tests were conducted before the study and on Day 79. The data were fitted to estimate beta-cell function and insulin sensitivity parameters using the SAAM II package integrating the oral minimal model (OMM), which was compared with Homeostatic Model Assessment (HOMA) analysis results.Results: Exenatide or PB-119 treatment, compared with their baseline, was associated with higher beta-cell function parameters (φb, φs and φtot), disposition index, insulin secretion rates, and a lower glucose area under the curve. High-dose PB-119 also has a higher insulin resistance parameter (SI) than the baseline, but HOMA-IR did not. For the homeostatic model assessment parameters, HOMA-IR showed no statistically significant changes within or between treatments. Only high-dose PB-119 improved HOMA-β after 12 weeks of treatment.After 12 weeks of treatment, PB-119 decreased glycemic levels by improving beta-cell function and insulin resistance.